Conflicting Preferences of Parents and Offspring Over Criteria for a Mate: A Study in Argentina - Buunk, Abraham P. (2010)
Current evolutionary research on human mating has largely ignored the fact that mating decisions may be heavily influenced by parents. Recent research, however, shows that parents and children may have conflicting mate preferences. Specifically, parents tend to have a relatively stronger preference for children to pair with mates with characteristics signaling high parental investment and cooperation with the in-group, whereas children tend to have a relatively stronger preference to pair with mates with characteristics signaling genetic quality. The present research among 242 young adults from Argentina showed that in this country the same parent-offspring conflict was observed as had been found previously in North America, the Netherlands, Uruguay, and Kurdistan. This result provides additional support for the universal character of this type of conflict. In addition, the present research expanded previous work by showing that the two conflict dimensions were indeed psychometrically independent, and that more conflict was reported by older and married participants. In addition, more conflict was reported among women who were more in favor of parental control over mate choice and among men who were higher in social comparison orientation.